3G & 4G Signal services assessments for fisherman community digital entrepreneurships at East Coast Malaysia - Badron, Khairayu; Ismail, Ahmad Fadzil; Hashim, Wahidah; Mohamad, Zaleha; Ahad, N. H.; Latiff, A.F.H.C. (PennWell Publishing Co., 2020)
The emerging of digital marketing and entrepreneurship is the main spotlight in today's business strategy. The villagers and fishermen are among the people that have original and delicious recipes for food production. Unfortunately, the current marketing technology has made them left out. This collaborative research project focusses on empowering the villagers and fishermen in Kuala Nerus, Kuala Terengganu Malaysia. Our partners from UNITEN and UMT will give training and knowledge about digital marketing. Our team will focus on the availability of the 3G and 4G signals in their area to ensure that this facility and new marketing strategy can be implemented. 15 sites of Kuala Nerus district have been chosen to be asses whether this signal is available and the signal strength is measured and analyze. The outcome of this study is important for the wellbeing of the residents in Kuala Nerus to utilize the 3G and 4G technology in their marketing strategy.